1976
DOI: 10.1104/pp.57.4.670
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Aspects of Imposition of Dormancy in Caryopses of Aegilops kotschyi

Abstract: Caryopses of Aegilops kotschyi Boiss. from different positions within the same spikelet differ greatly in their degree of dormancy. Imposition of this dormancy pattern is a correlative phenomenon within the spikelet, inasmuch as the uppermost developing caryopsis is least dormant and its development is associated with the dormancy status imposed on the lower (one or two) caryopses. Differences in pigmentation of the caryopses follow a corresponding pattern.Spikelets of Aegilops kotschyi Boiss. are normally com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…and Ae. triuncialis L. dimorphic pairs of seeds are found in the lower fertile spikelets, with one seed larger and lighter coloured than the other one (Datta et al ., 1970; Wurzburger et al , 1976; Dyer, 2004; Marañon, 1989). In Ae .…”
Section: Introductionmentioning
confidence: 99%
“…and Ae. triuncialis L. dimorphic pairs of seeds are found in the lower fertile spikelets, with one seed larger and lighter coloured than the other one (Datta et al ., 1970; Wurzburger et al , 1976; Dyer, 2004; Marañon, 1989). In Ae .…”
Section: Introductionmentioning
confidence: 99%
“…The germination characteristics of grass grains can be altered by surgical abscision of neighbouring grains (Wurzburger and Koller, 1973;Wurzburger and Leshem, 1976), or even by the removal of the glumes alone (Richardson, 1979). The germination characteristics of grass grains can be altered by surgical abscision of neighbouring grains (Wurzburger and Koller, 1973;Wurzburger and Leshem, 1976), or even by the removal of the glumes alone (Richardson, 1979).…”
Section: Introduction Parentalmentioning
confidence: 99%
“…Differences in germinability ('heteroblasty') due to position relative to other seeds is well known in the grasses where proximal grains in spikelets are usually the least dormant, for example in Aegilops ovata (Datta et al, 1970), Avena ludoviciana (Morgan and Berrie, 1970), and Poa trivialis (Froud-Williams and Ferris, 1987). In Aegilops kotschyi, the lower grain is the more dormant one (Wurzburger and Leshem, 1976). Curiously, Wurzburger and Koller (1976) found that in Aegilops kotschyi only the basal caryopsis (but not the upper one) was influenced by the external conditions imposed on the plant during seed development.…”
Section: Introduction Parentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the present findings imply that most probably positional seed dormancy effect in A. sterilis is not a specific desert adaptation against unpredictability of rainfall events. Heteromorphism in A. sterilis appears to evolve initially as a by-product of developmental constraints on seed size within a spikelet with small seeds having higher dormancy because of lower success in competition for essential metabolites or growth regulators [40] . Then, when oat plants started experiencing desert environment as either result of climate changes or range expansion, the positional seed dormancy revealed its usefulness and even necessity in a new environment and became one of the traits conferring adaptation to the desert climate unpredictability.…”
Section: Discussionmentioning
confidence: 99%